A new course for Japan's security policy: The historic decision on military armament - Alexandra Sakaki (Stiftung Wissenschaft und Politik (SWP), 2023)
In recent weeks, Japan's government under Prime Minister Kishida Fumio has implemented significant adjustments to the country's security policy. In December 2022, Tokyo published a new National Security Strategy along with two other defence-related strategic documents. In doing so, the government decided, among other things, to significantly increase Japan's defence budget to 2 per cent of its gross domestic product by fiscal year 2027. During bilateral alliance meetings in mid-January 2023, Japan and the United States addressed the implications of the new strategic documents and discussed possibilities for closer cooperation. By making far-reaching decisions such as on the acquisition of so-called counter-strike capabilities, Tokyo is seeking to respond to a rapidly deteriorating security environment. Even though some of the announced steps are indeed historic for Japan, they have been the topic of discussion for a while now and can therefore be seen as part of the evolution of Japanese security policy that has been occurring for years.
Keywords: 320; Japan; National Security Strategy; National Security Secretariat; Defense Buildup Program; Defence Buildup Program; Abe Shinzo; Nakasone Yasuhiro; Yamaguchi Natsuo; Fumio Kishida; Suga Yoshihide; Indo-Pacific; Kuril Islands; counter-strike capabilitiy; collective self-defence; Cyber Security